ANALYSIS OF RESIDUAL STRESS OF OIL AND GAS PIPELINE WITH TYPE I PLAIN DENT - WU Ying; TANG Na; MO Yu; QIU ChengZhi (Jixie qiangdu)
Maintain a high level of integrity and reliability of pipelines for oil and gas pipeline industry is essential. Due to various reasons,there will lead to the pipeline failure. Among them,pipeline defect is the main reason to the failure of itself.And dent defect is one of the general defect types. Therefore,it is necessary to conduct a further study on pipeline defect. In allusion to type I plain dent existing on oil and gas pipelines,analyzing the relationship between residual stress which is on type I plain dent area and various parameters. Based on fatigue life model,obtaining the influence rule of residual stress on pipeline fatigue life. It is significant for the design of new pipeline and maintenance of in service pipeline.